Development of software and hardware device of automated system of the process stabilization of arc dimensional processing - Савеленко, Григорій Володимирович; Єрмолаєв, Юрій Олексійович; Собінов, Олександр Георгійович; Гуцул, Василь Іванович (Technology audit and production reserves, 2015)
This article discusses the implementation of software and hardware device of automated system of the process stabilization of arc dimensional processing on EDM machines and some results of our research in this area are given. The main aim of research is to develop a functional structure of the program software and hardware devices and then checking its performance. Software and hardware device controller, based on a programmable logic controller, controls the automated electric supply tool electrode for EDM type of AMH-1. It is given the dependences that describe the control law according to which the programmable logic controller stabilizes and supports the arc parameters. The use of modern process control systems of EDM allows processing the materials with higher energy efficiency and less resource consumption. This paper proposes a variant of the problem solution of automated system of the process stabilization of arc dimensional processing. This system allows to automate the process of finding and maintaining the feed rate of the tool-electrode in an area close to the quasi-optimal performance of the process. The investigation results can be used by designers in the field of process automation of tool electrode submission during EDM machining of metals.